2021
DOI: 10.1186/s41606-020-00056-w
|View full text |Cite
|
Sign up to set email alerts
|

Quality of sleep and associated factors among people living with HIV/AIDS on follow up at Ethiopian Zewditu memorial hospital, 2018

Abstract: Background Sleep disturbance is a common complaint in people living with HIV/AIDS. Despite the influence of sleep disturbance on treatment adherence, quality of life, work productivity, risk of chronic illness, it remains under-recognized and under-studied in Ethiopia. Therefore it is necessary to produce scientific evidence to fill the knowledge gap and areas of management. The current study aimed to assess sleep quality and its associated factors among people living with HIV/AIDS. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Our study result is somewhat in agreement with previous studies that included HIV patients with HAART. 12,[14][15][16][17][18] In addition, the findings in the current study were similar to the results reported in China, which showed that the level of depression decreased from 23.0% at baseline to 14.0% at month 12 posttreatment. 11 Also consistent with a prospective observational study conducted by Downing et al, 12 the result showed that two sleep quality trajectory groups (bad sleep quality maintained and sleep quality negative change) were highly associated with depression.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study result is somewhat in agreement with previous studies that included HIV patients with HAART. 12,[14][15][16][17][18] In addition, the findings in the current study were similar to the results reported in China, which showed that the level of depression decreased from 23.0% at baseline to 14.0% at month 12 posttreatment. 11 Also consistent with a prospective observational study conducted by Downing et al, 12 the result showed that two sleep quality trajectory groups (bad sleep quality maintained and sleep quality negative change) were highly associated with depression.…”
Section: Discussionsupporting
confidence: 90%
“…Factors associated with poor sleep quality in PLWH, such as getting older and a higher intensity of depression, were also found in our study. 4 , 16 , 17 The relationship between getting older and poor sleep quality might be related to various factors, such as age-related sleep architecture and growth hormone changes. 33 Given the association between poor sleep and emotional disorders, there might be linkages between sleep, emotional regulation and alteration in the hypothalamic–pituitary–adrenal axis implication of psychopathology and sleep–wake cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing fatigue (and relatedly poor quality of sleep) and pain are somatic symptoms of depression which may be caused by HIV illness, and they can also make ART adherence worse [55]. Evidence from different settings in Ethiopia and South Africa shows increased odds of poor sleep quality among depressed PLWH [23,56]. Smaller impacts of these factors on self-reported adherence may not be surprising given that only 7% of our study sample reported high levels of depressive symptoms (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating the impact of different interventions to improve sleep quality, the authors demonstrate that improved sleep (in the form of naps) can alter decision-making (e.g., savings, increase attention to incentives, and reduce present bias) [21]. Evidence has shown that almost half of PLWH in some settings (such as in Ethiopia or Nigeria) report significant sleep disturbances, including difficulty falling asleep, waking up at night, and reduced sleep time [22][23][24]. Poor sleep may be a contributor to disease progression and further HIV-related morbidity primarily because of how it impairs the immune system and affects physical performance, cognitive function and emotion that could then influence medication adherence [25,26].…”
Section: Introductionmentioning
confidence: 99%